AN ANALYSIS OF THE ACTIVITIES IN ENGLISH TEXTBOOK (2017 REVISE EDITION) OF 11” GRADE SENIOR HIGH SCHOOL ENTITLED “STOP BULLYING NOW” PUBLISHED BY KEMENDIKBUD - Pakpahan, Sapta Friyanti; Purba, Indah Dewi Sartika; Pakpahan, Srilasima; Saragih, Erikson (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This research was conducted to evaluate the english textbookcontent of 11th grade Senior high school (2017 Revise Edition) Entitled "STOP BULLYING NOW"published by KEMENDIKBUD.This study used descriptive qualitative research approach.The data  source is 11th grade Senior high school english textbook and used the content analysisto evaluate the English textbook based on standard of KEMENDIKBUD.This study gathered the source data by using checklist instruments,which are consists of Textbook content,Presentation,Languange and Graphic Design.The data analysis resulted from the percentage of fullfilment scoreand gain 95% as the Good CategoryEnglish textbookand have been fulfilled the requirements of KEMENDIKBUD for eleventh grade senior high school.ThisEnglishtextbookEntitled"STOPBULLYINGNOW"itisaqualifiedbookbycontaingoodmaterialsbasedonMAGICConcepttheyareMotivating,AuthenticandAppropriate,GraphicandGraded,Interesting,InteractiveandIntegrated,ContextualizedandCreative.